SAMSAT DRIVE THRU MEMODERASI PENGARUH EFEKTIVITAS SISTEM PERPAJAKAN DAN KEPUASAN LAYANAN TERHADAP KEPATUHAN WAJIB PAJAK - Widyanti, Ni Made Ayu; Noviari, Naniek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
The lack of taxpayer compliance is a problem of the Motor Vehicle Tax collection process. This study aims to determine the effect of tax system effectiveness and service satisfaction on taxpayer compliance with Samsat Drive Thru as a moderating variable in the Samsat Tabanan Joint Office. The sample in this study consisted of 100 people, who were determined through the accidental sampling method. Data were collected by distributing questionnaires directly, then it is analyzed by using multiple linear regression analysis and moderated regression analysis. The results of multiple linear regression analysis show that tax system effectiveness and service satisfaction has a positive and significant effect on taxpayer compliance. The results of moderated regression analysis show that Samsat Drive Thru does not moderate the effect of tax system effectiveness and service satisfaction on taxpayer compliance. The Samsat Tabanan Joint Office is advised to intensify socialization regarding Motor Vehicle Tax, especially regarding Samsat Drive Thru services. This research was only conducted at the Samsat Tabanan Joint Office. Future researchers are advised to expand the scope of research so as to obtain better research results.